Exploring Teachers’ Pedagogical Integration Of Ict And Learner-Centred Teaching Approaches In Teaching Listening Skills In China - Fang, Meng (2025)
This qualitative study explores teachers’ pedagogical integration of Information and Communication Technology (ICT) and learner-centred teaching (LCT) approaches to teaching listening skills in China. the study identifies that pedagogical reasoning and institutional reasons influence the integration process.